Assessment of Caffeine Content in Tea and Coffee Brands Within the Palestinian Market Using HPLC Method - Waad Hisham; Haneen Nur; Hanadi Sinokort; Duha Haslamon; Alaa Khraiwesh; Abdel Qawasmeh (Future Postharvest and Food)
ABSTRACT Tea and Arabic coffee drinks are part of the daily routine for the Palestinian population due to deep cultural roots and their caffeine contents. The quality of the tea and coffee may be affected by the controlled‐long quarantine procedure followed during importation. Caffeine quantity in tea and coffee samples imported into Palestine has never been assessed. A documented HPLC method was used to determine caffeine contents in Palestinian commercially available imported brands of tea and coffee. The average caffeine content (%w/w) of tea and coffee samples was in the ranges of 0.94%–1.5% and 0.45%–0.74%, respectively. The limit of quantitation (LOQ) and the limit of detection (LOD) were found to be 1.3 and 0.5 ppm, respectively. The relative standard deviation (RSD) for repeatability was less than 5%, which is acceptable, whereas the recovery was more than 97%. The quantity of caffeine in commercially tea and coffee samples test were within the range documented in literature. This suggests that the tea and coffee quality in terms of their caffeine content has not been affected by the procedural/political issues surrounding occupied Palestinian territories. Whether other factors such as phenolic compounds and their attributed antioxidant capacity are affected is a subject of future studies.